The impact of skills having towards entrepreneurs’ perceptions among students and graduates at Private University College, Melaka / Norazman Harun, Noorizda Emellia Mohd Aziz and Maryam Mohd Esa - Harun, Norazman; Mohd Aziz, Noorizda Emellia; Mohd Esa, Maryam (2021)
This paper assesses the impact of skills having towards entrepreneurs perceptions among students and alumni at Private University College, Melaka. Methodology of this research by the author employed a quantitative approach and google form questionnaires are being used as the main instrument to distribute among the respondents who are students and alumni at Private University College, Melaka. The data were analysed using Statistical Package for Social Science (SPSS) software to obtain descriptive statistics. There have 160 respondents were participated in this research. All of them included students and alumni at Private University College, Melaka at different faculty where as there have six faculty in there. As the results, four out of eight variables of skill (decision making skills, risk taking skills, negotiation skills and sales techniques skills) have impact towards entrepreneurs perceptions among students and graduates at Private University College, Melaka.